Analysis of the Obedience of Personal Protective Equipment Usage to Prevent Occupational Disease among Cosmetic Workers - Dwijaningtyas, Srinata; Widowati, Evi; Pranoto, Pranoto; Saputra, Jumadil; Wintara, Jane Ayu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Cosmetic industry has a high risk of occupational diseases such as talcosis or respiratory disorders among the workers at PT X. Based on the preliminary study, respiratory disorders are indicated among the workers because of high level of dust powder from talc powder at the work place. Occupational diseases can be prevented such as by using correct and precise Personal Protective Equipment (PPE). Methods: The study aimed to determine the relationship between respiratory symptoms, knowledge, education, and job tenure with the obedience of PPE usage to prevent occupational disease because of talc powder among cosmetic division workers at PT X. The study used an analytical survey research method with a cross-sectional approach. The sample was 48 people using the Total Sampling technique. Statitiscal test using Chi-Square Test. Results: The result of the test showed there is a relationship between respiratory symptoms (p-value = 0,024) and knowledge (p-value = 0,006) variable with the obedience of PPE usage among workers (p-value = 0,006), to be found there is a respondence who has less knowledge regarding occupational safety and health is considered to have 18.3 times more risk of being disobedient in using PPE, while there is no relationship between education (p-value = 0,161) and job tenure (p-value = 1.000) with the obedience of PPE usage among cosmetic division workers at PT X. Conclusion: There is a relationship between respiratory symptoms and knowledge with the obedience of PPE usage among the workers, and it’s recommended to company owner to provide training for the workers about the importance of PPE usage that mainly corrects and precisely, also doing supervision and daily checking on the workers before, during, and after work.